Assessment of senescence of cut flowers in Chrysanthemum morifolium L. as judged from chlorophyll fluorescence characteristics of leaves on the same shoot - ZHANG Yan-qin; LI Fang; GUO Yan-ping; CHEN Kun-song (浙江大学学报. 农业与生命科学版)
Chlorophyll fluorescence parameters were measured by pulse-amplitude modulation (PAM) fluoremetry on the leaves of Chrysanthemum morifolium L. cut flowering shoots. Leaf chlorophyll degradation and flower ethylene release were measured at the same time. Specifically leaf senescence sequence was observed on leaves of different leaf positions. Along with the process of leaf senescence, the correlations between the decrease in chlorophyll content and chlorophyll fluorescence parameters Fv/Fm, ΦPSⅡ, Fv′/Fm′ and qP were remarkable (P<0.001). The significant decrease in parameter Fv′/Fm′, ΦPSⅡ and qP preceded or paralleled the chlorophyll degradation, and appeared before the rise of flower ethylene climacteric, while occurrence of decline in Fv/Fm was later than chlorophyll degradation. The results suggested that chlorophyll fluorescence parameters Fv′/Fm′, ΦPSⅡ and qP may provide a suitable, rapid and non-destructive criterion for estimation of leaf senescence.